PENDIDIKAN ISLAM DAN TANTANGAN KEBERAGAMAN: ANALISIS LITERATUR TENTANG STRATEGI MEMBANGUN TOLERANSI DI MASYARAKAT MULTIKULTURAL - Lizi Virma Surianti; Yudafriyenti, Elpita Sari , Mahyudin Ritonga , Julhadi, Sri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the role of Islamic education in addressing the challenges of cultural and religious diversity within multicultural societies, with a focus on strategies to foster tolerance. The research aims to analyze how Islamic educational frameworks can be adapted to promote inclusive and harmonious learning environments. A qualitative library research method was employed, involving a systematic review and critical analysis of relevant literature including books, journal articles, policy documents, and scholarly works by prominent Islamic thinkers. The findings reveal that Islamic teachings contain universal principles such as ta’āruf (mutual understanding), tasāmuh (tolerance), and consultation, which support peaceful coexistence. However, the implementation of these values in educational practices remains limited due to exclusive narratives in curricula, insufficient teacher training, and a lack of extracurricular programs promoting interfaith engagement. The study recommends policy revisions at both national and institutional levels, curriculum development integrating multicultural themes, and teacher training programs that emphasize pluralistic pedagogy.